2015
DOI: 10.3389/fpsyg.2015.00812
|View full text |Cite
|
Sign up to set email alerts
|

Cultural perspectives on children’s tadpole drawings: at the interface between representation and production

Abstract: This study investigated tadpole self-drawings from 183 three- to six-year-old children living in seven cultural groups, representing three ecosocial contexts. Based on assumed general production principles, the influence of cultural norms and values upon specific characteristics of the tadpole drawings was examined. The results demonstrated that children from all cultural groups realized the body-proportion effect in the self-drawings, indicating universal production principles. However, children differed in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…In general, our results are in line with the mixed cultural models of autonomous relatedness (Kagitçibasi, 1996; Gernhardt et al, 2015) and the trend, identified by Greenfield (2009, 2016), of a global rise in individualism as a result of the transformation of traditional rural contexts characterized by urbanization and the increase in the proportion of people living in urban areas, the rise in schooling, the increase in technology in people's daily lives, and the impact of money, commerce, and tourism. All of these factors have transformed traditional subsistence living for many communities including that of Zinacantan in los Altos de Chiapas (Greenfield, 1999; Greenfield et al, 2003, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In general, our results are in line with the mixed cultural models of autonomous relatedness (Kagitçibasi, 1996; Gernhardt et al, 2015) and the trend, identified by Greenfield (2009, 2016), of a global rise in individualism as a result of the transformation of traditional rural contexts characterized by urbanization and the increase in the proportion of people living in urban areas, the rise in schooling, the increase in technology in people's daily lives, and the impact of money, commerce, and tourism. All of these factors have transformed traditional subsistence living for many communities including that of Zinacantan in los Altos de Chiapas (Greenfield, 1999; Greenfield et al, 2003, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…In particular, these cultural models included (1) psychological autonomy (characteristic of Western, urban, middle-class contexts), (2) hierarchical relatedness (representative of non-Western, rural, traditional contexts), and (3) mixed cultural models of autonomous relatedness (e.g., non-Western, urban, middle-class contexts; migration contexts). Overall, the studies revealed that figure size, facial depiction, and gender-specific characteristics could be linked to the culturally shaped understanding of self and others in the respective cultural context (Gernhardt et al, 2014, 2015). Regarding the size of the figures drawn, for instance, rural Cameroonian children (who represent the cultural model of hierarchical relatedness, interdependent self-conception) draw themselves alone in a family picture smaller than urban German children (examples of the cultural model of psychological autonomy with an independent self-conception) (Rübeling et al, 2011).…”
Section: The Effects Of Schooling On Identitymentioning
confidence: 99%
“…More importantly, the present study accounts for the fact that not only did the older children of the sample draw the sun more often than their younger counterparts but they assign larger areas of the picture to represent it. In this connection, it is worth drawing attention to the fact that when it comes to analysing young children's drawings, the size of the elements drawn is not a trivial issue and this pictorial feature is supposed to be associated with the perceived importance and with the significance that the child attaches to the subject matter (Gernhardt et al 2015;Slee and Skrzypiec 2016). As for the implications that these ideas have in the sample under study, they suggest that the significant relevance that the older children attribute to the sun is the presumable reason which inspires them to draw bigger solar representations.…”
Section: Discussion Of the Data And Conclusionmentioning
confidence: 99%
“…One of the first steps of children's early symbolic drawing development is tadpole figures 10 . Consisting of two lines (legs) attached to a round form (head), the tadpole figure arises around 3 years of age 11 and is observed in Western as well in non-Western countries 12,13 . Thus, in the same way that children reorganize their spoken language to communicate efficiently, the appearance of these first recognizable drawings also allows them to be better understood by others 14 .…”
Section: Openmentioning
confidence: 99%